Changing Epidemiology of Common Cancers in Southern Iran, 2007-2010: A Cross Sectional Study. - Seyed Masoom Masoompour; Kamran B Lankarani; Behnam Honarvar; Seyed Hamidreza Tabatabaee; Mohsen Moghadami; Zahra Khosravizadegan (PLoS ONE, 2016)
We have evaluated the ever changing epidemiology of cancers in Fars province, Iran since the re-establishment of Fars cancer registry. Based on the collected data from all related sources in Fars province from 2007-2010 we calculated the cancer age-standardized rates per 100,000 person-years (ASRs). The results are presented as incidence rates of cases by site according to the International Classification of Diseases for Oncology (ICD-O), sex, age, crude rate, and ASRs. In women the total ASR was 41.70 per 100,000 from 1985-1989 which had increased to 55.50 and 95.46 during 1998-2002 and 2007-2010. The incidence of breast cancer in women during 2007-2010 was about two and four times higher than 1998-2002 and 1985-1989. The incidence of colorectal cancer in women during 2007-2010 was about three and five times higher than 1998-2002 and 1985-1989. In men the total ASR was 62.9 per 100,000 in 1985-1989 that increased to 64.50 and 101.48 during 1998-2002 and 2007-2010. Although stomach cancer was the most common cancer among men during 1985-1989 and 1998-2002, but in recent study bladder cancer was the most common cancer among men in Fars province. The incidence of colorectal cancer in men during 2007-2010 was about three times higher than 1998-2002 and 1985-1989. This study shows growing incidence of cancer in southern Iran. The colorectal cancer in both genders had increased and its pattern is similar to western countries. In men, bladder and prostate cancers had a growing rate and the incidences of these cancers in the present study were greater than stomach cancer.